Outcomes Reported After Surgery for Cauda Equina Syndrome: A Systematic Literature Review. Issue 17 (1st September 2018) - Srikandarajah, Nisaharan; Wilby, Martin; Clark, Simon; Noble, Adam; Williamson, Paula; Marson, Tony
Abstract : Study Design: This is a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Objective: To assess the outcomes reported in trials and observational studies of surgery for cauda equina syndrome (CES), and to inform the development of a core outcome set. Summary of Background Data: Scoping searches revealed that there were inconsistencies in which outcomes were reported and how they were measured in research studies for patients who had undergone surgery for CES. Methods: Ovid Medline, Embase, CINAHL Plus, and trial registries were searched from January 1, 1990 to September 30, 2016 with the term "cauda equina syndrome." Inclusion and exclusion criteria were applied according to study design, diagnosis, procedure, publication date, language, and patient age. Data extracted included demographics, study design, the outcomes reported, and their definition. We also assessed variation in the use of terminology for each outcome domain. Results: A total of 1873 articles were identified, of which 61 met the inclusion criteria. Of these, 737 outcomes reported verbatim were categorized into 20 core outcome domains and 12 subdomains with a range of 1 to 141 outcomes per outcome domain or subdomain. The most commonly reported outcomes were bladder function (70.5%), motor function (63.9%), and sensation (50.8%). Significant variation in the terms used for each outcome was documented, for example, bladder function outcome domain had 141 different terms. Conclusion: There is significant heterogeneity in outcomes reported for studies after surgery for CES patients. This indicates a clear need for the development of a core outcome set, which has been registered as number 824 on the COMET (Core Outcome Measure in Effectiveness Trials) database. Level of Evidence: 1 Abstract : Supplemental Digital Content is available in the text